1986
DOI: 10.1002/hlca.19860690302
|View full text |Cite
|
Sign up to set email alerts
|

Über Dienketene aus o‐Chinolacetaten

Abstract: (RS)- 6-acetoxl.-5,.6-dimeth?.l-, (RS)-6-ucetoxy-2,4,6-1rimeth~.l-, 3,4,6-tet r m n i 4 i j~l -. and (RS)- 6-oci~tox~-2,3,4,5,6-pentumeth~l-2,4-c~clo/ie.~udii~n-I-oni~.~ serve as representative educts.Thcrc arc two separate main photochemical routes conveniently designated as l(n*, n) or '(n*, n ) tracks. The latter may also he attained by sensitization and leads to phenols. The former, by a-cleavage furnishes dien-ketens as indispensable phototransients. Photolysis of dien-ketens follows one or more of three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

1987
1987
2006
2006

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 63 publications
0
10
0
Order By: Relevance
“…It has been suggested that oxyallyl compounds are intermediates in both thermal and photochemical rearrangements of bicyclo[3.1.0]hex-3-en-2-ones to phenols [25][26][27][28][29][30][31][32][33][34][35]. Some time ago, we studied the reaction pathway for the prototype rearrangement of bicyclo[3.1.0] hex-3-en-2-one (1a) to phenol (3a) in the gas phase at the CASSCF/CASPT2 level [36].…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that oxyallyl compounds are intermediates in both thermal and photochemical rearrangements of bicyclo[3.1.0]hex-3-en-2-ones to phenols [25][26][27][28][29][30][31][32][33][34][35]. Some time ago, we studied the reaction pathway for the prototype rearrangement of bicyclo[3.1.0] hex-3-en-2-one (1a) to phenol (3a) in the gas phase at the CASSCF/CASPT2 level [36].…”
Section: Introductionmentioning
confidence: 99%
“…Enols of acids were suggested as intermediates in the decarboxylation of a dicarboxylic acid,3a in the reductive debromination of a carboxylic acid,3b in the nitrosation of malonic acids,3c and in the Hell−Volhard−Zelinskii bromination of acids 3d. Enols of esters, acyl halides, and amides were suggested as intermediates in nitrosation of XCH 2 CO 2 Et (X = H, CN)4a and addition of alcohols 4b or H−Hal 4c to ketenes, water addition to ketenimines,4d and electrophilic substitution of malonamide,4e respectively. A conjugated enol amide was observed by UV in a low-temperature photolysis of a dienone in the presene of an amine 4f…”
Section: Introductionmentioning
confidence: 99%
“…548,11 This compound has a well-documented history of photochemistry546 and a known quantum yield ( = 0.53 (365 nm, 20 °C))55 at a specific concentration. 56 We observed only one isomer,57 and we were able to reproduce this quantum yield (0.52).…”
Section: Methodsmentioning
confidence: 68%